Pengaruh Kebijakan Hutang Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada PT Ultrajaya Milk Industry And Trading Company Tbk Periode 2014- 2023 - Mega Julian, Bunga; Jamaluddin Jamaluddin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine whether there is an effect of debt policy and investment decisions on company value at PT Ultrajaya Milk Industry And Trading Company Tbk. This is a quantitative study with a causal associative approach. The data used in this study is secondary data sourced from the financial data of PT Ulrajaya Milk Industry And Trading Company Tbk for the period 2014-2023. The data analysis method used in this study is multiple linear regression analysis with the assistance of the Statistical Product and Service Solution (SPSS) program version 26. The results of the study indicate that, partially, debt policy does not have a significant effect on company value, as evidenced by a significance value of 0.059, which is greater than the sig. 0.05, and the t-calculated value (2.256) < t-table (2.447). Meanwhile, investment decisions have a significant effect on company value, as evidenced by a significance value of 0.004, which is smaller than the sig. value of 0.05, and the t-calculated value (4.213) > t-table (2.447). Meanwhile, simultaneously, it shows that debt policy and investment decisions have a significant effect on company value, as evidenced by a significance value of 0.008, which is smaller than the sig value of 0.05, and the Fcount value (10.353) > Ftable (4.74).